ICU nurses’ burnout, organizational commitment, turnover intention and hospital workplace violence: A study in Sichuan province, China - Tiemei Wang (2019)
The study aims to research the relationship between burnout, organizational commitment and turnover intention. Additionally, hospital workplace violence and its influencing factors were also explored. A quantitative analysis was conducted with a survey of 305 ICU nurses in tertiary hospitals in Sichuan Province, China. The results reveal that (1) burnout is positively related to turnover intention; (2) organizational commitment is negatively correlated with turnover intention; (3) organizational commitment negatively moderates the effect of emotional exhaustion on turnover intention; (4) continuance commitment has a negative moderation effect on the relationship between emotional exhaustion on turnover intention; and (5) 77.7% of ICU nurses have experienced hospital workplace violence, among which professional title, gender, length of service and employment form are contributors.